2015
DOI: 10.21914/anziamj.v56i0.9345
|View full text |Cite
|
Sign up to set email alerts
|

Cauchy integrals for computational solutions of master equations

Abstract: Cauchy contour integrals are demonstrated to be effective in computationally solving master equations. A fractional generalization of a bimolecular master equation is one interesting application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Such an unfavourable situation can certainly arise. It is demonstrated to happen on the parabolic contour displayed here in Figure 6 for bimolecular reactions [12]. The issue is also addressed by In'T Hout and Weideman [7] for Black-Scholes models.…”
Section: Estimating the Field Of Valuesmentioning
confidence: 68%
See 1 more Smart Citation
“…Such an unfavourable situation can certainly arise. It is demonstrated to happen on the parabolic contour displayed here in Figure 6 for bimolecular reactions [12]. The issue is also addressed by In'T Hout and Weideman [7] for Black-Scholes models.…”
Section: Estimating the Field Of Valuesmentioning
confidence: 68%
“…The process is a Markov process if and only if the waiting times are exponential random variables, in which case the K(j, t) appearing in the convolutions in (2) are Dirac delta distributions and (2) reduces to the usual equation in (1). In the special case of Mittag-Leffler waiting times, (2) can be re-written as [12,13]:…”
Section: Introductionmentioning
confidence: 99%
“…A simple example of a graph Laplacian on a line of nodes appears in [40], and, like the matrix exponential, it has been shown that a Mittag-Leffler function [16] of a graph Laplacian matrix is also a stochastic matrix [33]. All of this suggests research into non-Markovian generalisations of Gillespie-like stochastic simulation algorithms allowing waiting times not exclusively drawn from an exponential distribution [31]. It is known that if we generalise (2.1) to a Caputo fractional derivative of order 0 < α < 1, d α /dt α , then the matrix exponential is generalised to the Mittag-Leffler function E α , so that (2.1) becomes d α p/dt α = Ap with solution p(t) = E α (t α A)p(0).…”
Section: Matrix Functions Of Graph Laplaciansmentioning
confidence: 99%
“…Of course, similar reasoning applies also to a product y = Zu. The only difference vis-á-vis (30) is that now y…”
Section: Evaluating the Exponential Via (29)mentioning
confidence: 99%
“…Putting α ← 1 in these formulas recovers the survival time distribution, cdf , and waiting time density, corresponding to an exponential distribution with parameter λ and mean value 1/λ. Unlike the exponential case, equation (37) shows that the Mittag-Leffler function and hence also the solution of (7) is not differentiable at t = 0 + . In general care must be taken when differentiating near zero, as happens later in (59).…”
Section: A Probabilistic Interpretationmentioning
confidence: 99%